2015
DOI: 10.1186/s13293-015-0031-0
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in gut fermentation and immune parameters in rats fed an oligofructose-supplemented diet

Abstract: BackgroundMechanistic data to support health claims is often generated using rodent models, and the influence of prebiotic supplementation has largely been evaluated using male rodents. Given that sex-based differences in immune parameters are well recognized and recent evidence suggests differences in microbiota composition between sexes, validation of the effectiveness of prebiotics merits assessment in both males and females. Here, we have compared the effect of oligofructose (OF) supplementation on the fec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
70
2
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(81 citation statements)
references
References 81 publications
(92 reference statements)
6
70
2
3
Order By: Relevance
“…For example, ICR (Swiss albino) males have been reported to be more vulnerable to microbiota infections and development of inflammation than corresponding females . A few animal studies have, indeed, demonstrated a correlation between microbiota diversity and sex, and in response to different nutrients . Human studies have also indicated a difference in overall microbiota communities in the gut or of specific bacteria related to gender .…”
Section: Discussionmentioning
confidence: 99%
“…For example, ICR (Swiss albino) males have been reported to be more vulnerable to microbiota infections and development of inflammation than corresponding females . A few animal studies have, indeed, demonstrated a correlation between microbiota diversity and sex, and in response to different nutrients . Human studies have also indicated a difference in overall microbiota communities in the gut or of specific bacteria related to gender .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, endothermic animals studies have also revealed that the gut microbiota composition between gender are different [2124, 33]. The difference in gut microbiota between sexes, may be hormones associated with each sex that might affect the composition of the gut microbiota [34, 35].…”
Section: Discussionmentioning
confidence: 99%
“…Male and female rodents, for example, metabolise a diet supplemented with the prebiotic oligofructose (OF) differently, with females having higher levels of Bacteroidetes compared to males [90]. Faecal buty-rate levels are also increased in males, and liver IgA, IL-6 and caecal IL-6 levels are higher in males, while anti-inflammatory IL-10 levels are higher in females [90]. Further, mice given an oral anti-ageing oil treatment show sex-based differences in GIT microbiota modulation [46].…”
Section: Treatments For Dysbiosis Should Consider the Sex Of The Recimentioning
confidence: 99%